Mutual rights between spouses: a juristic analytical study = الحقوق المشتركة بين الزوجين ي الشرع : دراسة فقهية تحليلية - Mat Jubri@Shamsuddin, Mustafa; Sitiris, Miszairi (2021)
The purpose of this research is to present the rights that spouses share during their marriage and to study them in the light of Islamic jurisprudence. This is through answering questions of what are the mutual rights between spouses? What are their types? What is the legal evidence for these types? What are legal considerations in legitimating these rights? Why does Islam make these rights equally to both husband and wife? The purpose of answering these questions is to present that Islam recognizes such equality between male and female in their rights and responsibilities. This study consists of three chapters, while the first describes the meaning of mutual rights between spouses, the second illustrates the types of mutual rights between spouses, and the third touches the legal rulings of these rights and their objectives. This study follows the inductive method in collecting and compiling related data, and analytical method in deducting results and findings from this data.